South (2016) et North (2018) de Frank Owen : diptyque post-apocalyptique américain ou sud-africain ? - (:unkn) unknown (My University, 2021)
This chapter examines two post-apocalyptic novels by South African writer Frank Owen. It shows how the author recycles classic motifs of post-apocalyptic literature, but also of other artistic genres, to explore American and South African identities.Cet article propose une lecture du diptyque sud-africain "South" et "North" de Frank Owen. Il examine la façon dont l'auteur recycle et revisite des motifs classiques de la littérature post-apocalyptique, mais aussi d'autres formes artistiques, pour explorer les identités américaines et sud-africaines.
Keywords: African Research